O desafio da agroindustrialização no Tocantins: estudo de caso da cadeia produtiva da aquicultura a partir da abordagem de Cadeia Global de Valor (Global Value Chain – GVC) - Castilho, Maurício de Araújo (Universidade Federal do Tocantins, 2018)
This work analyzed the bottlenecks of the industrialization of agricultural products derived from the aquaculture production chain in the state of Tocantins, Brazil, using the Global Value Chain (GVC) approach. It considered the characteristics that influence the competitiveness of the chain actors, since it presents production growth and potential characteristics for the continuity of this growth, thus becoming an alternative of employment and income generation and possible value aggregation through agro industrialization and strengthening of local actors. The methodology addressed the exploratory survey and interviews, data analysis and triangulation based on the GCV approach, seeking to evidence changes in the competition among companies, in understanding how and where the actors position themselves to gain market and participation and in determining how actors position themselves by means of the upgrading to achieve higher values of products and services. Based on the findings, two characteristics are identified in the behavior of the fish processors, where a portion of these actors is optimistic, aimed at intensifying the verticalization of production, with a high degree of corporate individualism, developing alternatives for upgrading through the products value addition and markets expansion, while another part of these same actors presents stagnation as to volumes and prices. Moreover, it is a market that face great illegal competition and characteristics of multiple types of governance and large informal competition. Such conditions impose great difficulties for the expansion of local agroindustry, and presents a considerable threat to the economic sustainability of the activity of the inspected fish processors.